Implementation of the Rights of Justice Collaborators to Get Reduced Sentences in the Crime of Murder - Dany Ardiansah Putra; Wahyu Prawesthi; Dedi Wardana Nasoetion (Civiliza Publishing, 2026)
The concept of a Justice Collaborator (JC) has become an important instrument in criminal law enforcement, particularly in uncovering complex crimes. A justice collaborator refers to a perpetrator who cooperates with law enforcement authorities by providing significant information to reveal a criminal act and identify other perpetrators. In Indonesia, the recognition of justice collaborators is regulated in Law Number 13 of 2006 as amended by Law Number 31 of 2014 concerning the Protection of Witnesses and Victims, as well as Supreme Court Circular Letter Number 4 of 2011. This study examines the implementation of the rights of justice collaborators to obtain sentence reduction in cases of murder and analyzes the legal considerations applied by judges in granting such leniency. This research employs a normative legal method using statutory and conceptual approaches. Primary legal materials consist of relevant laws and regulations, while secondary materials include legal doctrines and scholarly articles. The data are analyzed qualitatively through descriptive analysis. The results indicate that although justice collaborators are legally entitled to special protection and the possibility of sentence reduction, their implementation in murder cases is not automatic and depends heavily on judicial discretion. Judges consider several factors, including the significance of the information provided, the role of the offender in the crime, and the consistency of cooperation during the investigation and trial process. The study concludes that clearer legal standards and consistent judicial application are necessary to ensure legal certainty and fairness in granting sentence reductions to justice collaborators in murder cases.